The Digital Religious Narratives: Psychological Analysis of al-Najā’ib (Heavenly Conveyances) Hadith in @alqariomarali Instagram Account: Narasi Keagamaan Digital: Analisis Psikologis terhadap Hadits tentang al-Najā’ib (Kendaraan Surga) di Akun Instagram @alqariomarali - Anna Nurfitroh; Murtini, Nurul Budi; Abdullah, Akhmad Fahrisan Luthfi (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
The narrative concerning al-Najā’ib (heavenly conveyances) presented by the Instagram account @alqariomarali has triggered a complex discussion. Beyond the validity as a fundamental aspect of hadith studies, the psychological dimension emerging through the comments of the digital public (the audience) further reveals the significant complexity of hadith discourse within digital spaces. However, the scarcity of sources that elucidate this specific discourse presents a primary challenge in comprehending the intricacies involved. In this context, two questions form the starting point of the study: First, how does the hadith about al-Najā’ib engage with Muslim society within the digital space of Instagram? Second, what are the psychological implications of the al-Najā’ib religious narrative for Muslim society? Employing a descriptive-analytical approach based on library research, this study combines methodological verification from the science of hadith with the theories of Emotional Contagion and Collective Effervescence to analyze the dissemination of religious emotion within online communities. The findings indicate that, although the hadith is classified as dha’īf, its propagation on Instagram forms a kind of “virtual majelis dzikir” that has the potential to foster positive emotions, social cohesion, and serious motivation for worship among the digital populace. Nevertheless, to maintain a dynamic of critical discourse toward religious narratives, strengthening literacy is essential to support religious outreach that is simultaneously empathetic and critically engaged with source validity.